Automatic high order aberrations correction for digital holographic microscopy based on orthonormal polynomials fitting over irregular shaped aperture. (22nd March 2019) - Yang, Zhongming; Liu, Zhaojun; He, Weilin; Dou, Jiantai; Liu, Xin; Zuo, Chao
Abstract: We propose an automatic high-order aberration correction method for digital holographic microscopy based on orthonormal polynomial fitting over an irregular-shaped aperture. The corner detection technique is used to detect the specimen-free area for orthonormal polynomials over an irregular-shaped aperture. The high-order aberration correction method is completely automatic and requires only a single hologram. Experiments showed that in aberration correction, both lower-order phase curvatures and high-order aberrations could be corrected without requiring extra devices. Numerical simulations show that the proposed method provides more accurate high-order aberration correction than aberration correction methods based on least squares fitting with standard polynomials. Experimental results demonstrate the feasibility of using the proposed method for analyzing human macrophage cells.